Embryonic stem cells: Review - Ozel, H. Banu; Ozan, Enver; Dabaka, D. Ozlem (Ortadogu Ad Pres & Publ Co, 2008)
Embryonic stem cells are unique pluripotent cells derived from the inner cell mass of mammalian blastocysts. Their abilities of renewal and differentiate to cells of the three germ layers provided hope for their use in regenerative medicine. Although human embryonic stem cells are valuable for transplantation therapy of various diseases, some factors limit their clinical use. In this review, properties of embryonic stem cells and techniques for their derivation, propagation and differentiation are summarized. In addition, genetic manipulation methods to obtain transplants that are genetically compatible with the host are examined. Stem cell studies are among the most promising areas of research for human health; however, further studies are needed before clinical practice.
Embriyonik kök hücreler
Keywords: embryonic stem cells; pluripotent stem cells